Nurses' response to spiritual needs of cancer patients. (October 2020) - Zumstein-Shaha, Maya; Ferrell, Betty; Economou, Denice
Abstract: Purpose: In this qualitative study, nurses from the United States of America (USA) and Switzerland were asked to recount their spiritual care experiences with cancer patients and their own responses to their patients' spiritual needs. Recent advances in cancer care have highlighted the importance of spirituality and spiritual care as part of quality palliative care from the time of a patient's diagnosis through end of life. Nurses who play an important role in supporting patients, describe their own discomfort when confronting their patients' spiritual needs. Methods: A qualitative survey was used to collect narratives of nurses' experiences in responding to spiritual care needs (n = 62). The accounts were analyzed using thematic analysis. Results: Nurses identified patients as having spiritual needs and their own experiences in addressing spirituality or religion. Patients sought meaning in their illness, which, they believed, led to disease acceptance. Nurses reported their patients' struggles with challenging disease situations and their own challenges in addressing patients' spirituality/religion. With experience, nurses developed ways of talking with patients about spirituality/religion, which profoundly impacted their own lives and resulted in personal growth. Conclusion: Patients' spirituality was identified by nurses who tried to address patients' spiritual needs drawing on existing resources. For nurses, supporting patients in their spirituality and finding meaning in the disease situation eventually led to disease acceptance. Highlights: Spirituality is one key dimension of quality patient care. Nurses have the opportunity to assess spiritual needs and to respond to these needs. Additional education is needed to prepare nurses to provide spiritual care.